Assessment of green infrastructure measures to reduce stormwater runoff and enhance multiple benefits in urban areas - Gomez, Jose Manuel Patino; Sutat Weesakul; Vojinovic, Zoran; Thammarat Koottatep; Duc Nguyen Hoang; Torres, Arlex Sanchez; COLFUTURO (Pathum Thani, Thailand : Asian Institute of Technology, 2017)
More than half of the world{u2019}s population live in cities, urbanization is only increasing, putting high pressure on water and ecosystems. Our future depends on the quality of our cities and the challenge is to keep them livable, healthy and in harmony with the environment. Natured-based solutions (eg. LID, BMP, SUDS, WSUD, GI)are currently under research and development to treat water as a resource that must be preserved and maintained, by mimicking the natural water cycle before the development, conserving the natural runoff, water quality and having an impact on additional benefits like groundwater recharge, urban heat island effect, air pollution, amenity and aesthetics, recreation, pumping costs, rainwater harvesting among others. This research proposes a comprehensive framework for selecting and evaluating combination of GI measures to reduce the stormwater runoff and enhance additional benefits. More than 24 tools were identified and categorize, then according to four criteria where selected to be part of the framework. The application of the framework on a study case show that can be achieve up to 20% reduction on volume and peak flow runoff with a covering area of only 5.6 %of the total study area. The most cost-effective GI measures where bio-retention, rain garden and pervious pavement.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Urban Water Engineering and Management jointly offered by the Asian Institute of Technology, Thailand and UNESCO{u2013}IHE, The Netherlands
Thesis (M. Sc.) - Asian Institute of Technology - UNESCO-IHE, 2017
A thesis submitted in partial fulfillment of the requirements for the Degree of Master of Science in Urban Water Engineering and Management jointly offered by the Asian Institute of Technology, Thailand and UNESCO-IHE, The Netherlands
Keywords: Urban runoff -- Management